An In-Depth Analysis of the Oral Reading Comprehension of the Grade 7 Students of Liceo de Pulilan Colleges Inc. - Jesus, Dennis A. De; Isleta, Angelica Joy M.; Laoyon, Gresa J.; Reyes, Henderson DN.; Bugauisan, Julie Ann L.; Caasi, Richard E. (NPRC Journal of Multidisciplinary Research, 2025)
Literacy, defined as the ability to read and write, was considered a vital skill for personal success and societal development. In the Philippines, the literacy rate was reported at 96% in 2019 (World Population Review, 2024). However, reading comprehension remained a significant concern. According to the 2022 Program for International Student Assessment (PISA), the Philippines ranked 76th out of 81 participating countries in reading comprehension (Servallos, 2023). This was not a new trend; in the 2018 PISA, the country had ranked the lowest among 79 nations, indicating a persistent challenge in improving reading skills among Filipino students. This study provided an in-depth analysis of the oral reading comprehension skills of Grade 7 students at Liceo de Pulilan Colleges Inc. It aimed to determine the factors that affected their reading proficiency and to identify strategies to enhance their comprehension abilities. Using a mixed-methods approach, the research assessed student performance through standardized tests, classroom observations, and teacher interviews. The findings revealed significant gaps in reading comprehension, which were attributed to several factors, including teaching methods, language exposure, socio-economic conditions, and limited access to reading resources. The study emphasized the need for targeted interventions and instructional improvements to bridge these gaps and foster a higher level of literacy among students. Ultimately, the research contributed to developing effective educational policies and practices that aimed to enhance reading skills, supporting students' academic success and lifelong learning potential.